Zastosowanie witrektomii w leczeniu endogennego grzybiczego zapalenia wnętrza gałki ocznej u pacjentki po przeszczepie nerek - Oficjalska-Młyńczak, Jolanta; Turno-Kręcicka, Anna; Muzyka-Woźniak, Maria; Teklak, Dorota (Klinika Oczna / Acta Ophthalmologica Polonica, 2003)
The authors present a case of fungal endophtalmitis in the immunospressed patient after renal transplantation. The treatment comprised pars plana vitrectomy with silicone oil tamponade, peribulbar injections of Fungizone and intravenous Diflucan. Diagnostic and therapeutic difficulties in endogenous endophtalmitis are discussed.